Surface-functionalized 3D porous rGO-polysaccharide sphere composites for rapid selective protein adsorption from crude biological liquid - Lee, Hyunjung; Lee, Uijin; Moon, Byung Joon; Lee, Sang Hyun; Shin, Yong-Beom (ELSEVIER, 2020)
A novel protein adsorbent was developed by the surface modification of porous rGO-polysaccharide sphere composites with Coomassie Brilliant Blue G250 (CBB-G250). The advanced protein adsorbent combined selectively with proteins from crude bacteria lysate within 10 min, while deoxyribonucleic acid (DNA) was not adsorbed. Thus, protein and DNA in complicated biological samples were separated very quickly and easily during mild mixing treatment with the surface-functionalized rGO-polysaccharide sphere composites. The rGO in the porous sphere composites plays a key role as a linker in the adsorption of CBB-G250 on the composites and makes the CBB-G250 dye bind protein selectively from crude samples. It was confirmed that selective protein adsorption was only possible when the CBB-G250 dye had a chance of interaction with rGO. In addition, the CBB-G250-functionalized rGO-polysaccharide sphere composites could capture whole pathogens because of binding to the surface proteins of the pathogens. Therefore, the surface-functionalized rGO-polysaccharide sphere composites are good candidates for application in simple and efficient methods for the separation and purification of DNA in crude pathogen lysate and for the removal of whole pathogens by selective binding with proteins in the area of rapid pathogen detection and diagnosis.
Keywords: IMMUNOMAGNETIC SEPARATION; PCR; WATER; OXIDE; DNA; PHARMACEUTICALS; PERFORMANCE; SALMONELLA; EXTRACTION; PATHOGENS